Perancangan dan Implementasi UI/UX Website Edukasi Kesehatan Balita Menggunakan Metode Design Thinking - Mufadhal Faraz Addhifa; Nur Adi, Taufik; Lailatuth Thohiroh, Elvira (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
This research examines the design and implementation of user interface (UI) and user experience (UX) on a toddler health education website using a design thinking approach. The main problem studied is the low accessibility and interactivity of toddler health information available online, which leads to a lack of parental understanding of the nutritional needs of toddlers. This research aims to design an intuitive UI and satisfying UX to increase parents' participation and understanding of toddler health information. The research method consists of three main stages: problem identification, design, and implementation, which include data collection through literature review, online survey, and in-depth interviews. The design process followed the design thinking methodology with empirical steps: empathize, define, ideate, prototype, and test. Data obtained from surveys and interviews were used to inform the creation of an initial prototype, which was then tested to obtain user feedback. Evaluation was conducted using usability testing and System Usability Scale (SUS) methods, resulting in an average score of 83.5, indicating an excellent level of user acceptability of the developed design. The findings of this research indicate that the simplified, easy-to-use, and interactive UI/UX design successfully addresses the challenges of accessing under-five health information. The resulting website, known as "Pelita", provides valid and reliable health information content, as well as additional features such as nutrition guidance, health service locations, and consultation services. This research not only resulted in an innovative and relevant design, but also increased parents' understanding and active participation in maintaining the health of their toddlers.